Islamic Parenting Management and Digital Literacy Integration to Strengthen Family Roles - Dirlam, Dirlam; Norman, Efrita; Syarifudin, Aip; Duryat, Masduki; Haris, Mohammad Akmal (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2026)
The rapid expansion of digital technology has reshaped parenting practices, creating new demands for families to guide children responsibly while maintaining Islamic educational values. This study aims to examine how Islamic parenting management is integrated with digital literacy to reinforce parental roles in children’s academic development. Using a qualitative case study approach, data were gathered through interviews, observations, and document analysis involving parents, teachers, and psychological counselors. The findings reveal that combining Islamic parenting principles with digital tools enhances parents’ capacity to monitor children’s development, maintain consistent routines, and strengthen value-based communication at home. Digital platforms also increase parental reflection and enable more responsive school–family interactions. This study offers novelty by demonstrating that integrating faith-based guidance with digital literacy provides a culturally grounded model that prior studies typically do not address, examining these elements separately. Theoretically, the study enriches the understanding of how religious values can be operationalized within technology-assisted parenting. Practically, the findings suggest that schools can improve family engagement by designing structured, faith-oriented programs supported by accessible digital tools.